INCONSISTENCY OF CRIMINAL ELEMENTS IN THE ARTICLE ON GRATIFICATION COMMITTED BY CIVIL SERVANTS IN RELATION TO THE LAW ON CRIMINAL ACTS OF CORRUPTION - Muhammad Ali Akbar Panjaitan; Adi Mansar; Mhd Teguh Syuhada Lubis (NOMOI Law Review, 2026)
Law No. 20 of 2001 Amending Law No. 31 of 1999 on the Eradication of Corruption still contains inconsistencies in its provisions, particularly regarding gratification, specifically in Article 5(2) and Article 11, which share the same elements as Article 12(a) and (b), as well as Article 6(2), which shares common elements with Article 12(c); however, each is subject to different criminal penalties, thereby creating legal uncertainty and opening the door to abuse of authority by law enforcement officials in the application of these provisions. This study employs a normative legal method through a legislative, theoretical, and legal conceptual approach to analyze the offense of gratification committed by civil servants, the application of its criminal sanctions, and the reformulation of legal provisions regarding gratification in corruption-related criminal offenses. The research findings indicate that the offense of gratification consists of four main elements: the perpetrator being a civil servant or public official; the act of receiving gratification; the existence of a relationship with an official position that conflicts with duties or obligations; and the failure to report the gratification to the Corruption Eradication Commission (KPK) within 30 working days of receipt. Various obstacles were identified in the enforcement of sanctions, including internal legal system obstacles—such as legal substance, institutional issues, and legal culture—as well as external obstacles in the form of sociological factors, technical challenges in law enforcement, and overlapping regulations.